Organizational Dynamics of Islamic Boarding Schools: Integrating Traditional Values with Technology - Puput Anggraini; Nani Septiana; Ahmad Khotib; Ainur Rofiq (Universitas Nurul Jadid, 2024)
This study examines the dynamics of the Darussalam Islamic Boarding School organization in the digital era with a convergence model approach, especially in using digital technology to support management and education. This study uses a qualitative method with a case study design. Data were collected through observation, in-depth interviews, and documentation analysis involving key informants such as Islamic boarding school caretakers, administrators, students, and guardians of students. The study results indicate that digitalization has brought significant changes in the organizational structure of Islamic boarding schools, communication patterns between actors, and management strategies, although traditional values are still maintained. The convergence model is applied through technology integration to strengthen internal and external communication, such as using digital media in learning and managing student information. The implications of this study show the importance of Islamic boarding school adaptation to technological developments to improve management effectiveness and competitiveness while offering guidance for traditional-based educational institutions in facing the challenges of the digital era.